3′-UTR Shortening Contributes to Subtype-Specific Cancer Growth by Breaking Stable ceRNA Crosstalk of Housekeeping Genes - Fan, Zhenjiang; Kim, Soyeon; Bai, Yulong; Diergaarde, Brenda; Park, Hyun Jung (Frontiers in Bioengineering and Biotechnology, 2020)
Shortening of 3ʹUTRs (3ʹUS) through alternative polyadenylation (APA) is a post-transcriptional mechanism that regulate expression of hundreds of genes in human cancers. In breast cancer, different subtypes of tumor samples, such as estrogen receptor positive and negative (ER+ and ER-), are characterized by distinct molecular mechanisms, suggesting possible differences in the post-transcriptional regulation between the subtype tumors. In this study, based on the profound tumorigenic role of 3ʹUS interacting with competing-endogenous RNA (ceRNA) network (3ʹUS-ceRNA effect), we hypothesize that the 3ʹUS-ceRNA effect drives subtype-specific tumor growth. However, we found that the subtypes are available in different sample size, biasing the ceRNA network size and disabling the fair comparison of the 3ʹUS-ceRNA effect. Using normalized Laplacian Matrix Eigenvalue Distribution, we addressed this bias and built the tumor ceRNA networks comparable between the subtypes. Based on the comparison, we identified a novel role of housekeeping (HK) genes as stable and strong miRNA sponges (sponge HK genes) that synchronize the ceRNA networks of normal samples (adjacent to ER+ and ER- tumor samples). We further found that distinct 3ʹUS events in the ER- tumor break the stable sponge effect of HK genes in a subtype-specific fashion, especially in association with the aggressive and metastatic phenotypes. Knockdown of NUDT21 further suggested the role of 3ʹUS-ceRNA effect repressing HK genes for tumor growth. In this study, we identified 3ʹUS-ceRNA effect on the sponge HK genes for subtype-specific growth of ER- tumors.